CD8+ T cells Sabotage their own Memory Potential through IFN-γ-dependent modification of the IL-12/IL-15Rα axis on Dendritic Cells - Kohlhapp, Frederick J. (2012)
CD8+ T cell responses have been shown to be regulated by dendritic cells (DCs) and CD4+ T cells leading to the tenet that CD8+ T cells play a passive role in their own differentiation. In contrast, by using a DNA vaccination model, to separate the events of vaccination from those of CD8+ T cell priming, we demonstrate that CD8+ T cells, themselves, actively limit their own memory potential through CD8+ T cell-derived IFN-γ-dependent modification of the IL-12/IL-15Rα axis on DCs. Such CD8+ T cell-driven cytokine alterations result in increased T-bet and decreased Bcl-2 expression, and thus decreased memory progenitor formation. These results identify an unrecognized role for CD8+ T cells in the regulation of their own effector differentiation fate and a previously uncharacterized relationship between the balance of inflammation and memory formation.